Transatlantic crisis, crisis of representation, crisis of hegemony (1808-1900) - Rincón, Carlos (Estudios de Filosofía, 2008)
My presentation is structured in four parts. The project began by seeking to describe and give categorical specification to a series of differential phenomena, which by comparison and contrast ended up forming constellations. We did not know whether to constitute them in anomalies or if they could be something else. I will refer only to three of them. The first touches on the way in which from 1809 and until the 1820s the new political reality was mediated and communicated through symbols that at the level of daily life and attempts at institutionalization, was in the process of being established. For it is known that in order to impose its validity claims and to maintain and reproduce itself, all political systems and orders require symbolic representations. An allegorical figure of a woman, as a representation of the Homeland, Liberty or the Republic, provided the Revolution of the thirteen North American colonies, and the French Revolution throughout its entire trajectory, up to the Consulate and the Empire, a basic symbolic structure. With the help of this female figure, they were able to establish both indications of meaning and chains of equivalence and differences, at the time when the sovereign Monarch and his symbols were replaced by popular sovereignty. [Fragment]